Effect of Bioglass Nanoparticles on the Properties and Bioactivity of Poly(Lactic Acid) Films - Orihuela-Diaz, P; Ortiz-Nunez, J; Zapata-Ramirez, P; Canales-Arévalo, D; Saavedra-Gonzalez, M (John Wiley and Sons Inc., 2020)
Bioglass nanoparticles (n-BGs, 54SiO2:40CaO:6P2O5 mol %) with about 27 nm diameter were synthesized by the sol–gel method and incorporated into a poly(lactic acid) (PLA) matrix by the melting process in order to obtain nanocomposites with filler contents of 5, 10, and 25 wt %. Our results showed that during the cooling scan, the crystallization temperature (Tc) of the PLA/n-BG nanocomposites decreased 13°C as compared to neat PLA. The presence of nanoparticles also decreased the thermal stability of the PLA matrix, as nanocomposites presented up to about 20°C lower degradation temperatures in a nitrogen atmosphere. The presence of n-BG increased the stiffness of the polymer matrix, and for instance the composite with 25 wt % of filler presented about 52.6% higher Young s modulus than neat PLA. n-BG incorporation into PLA increased also the hydrolytic degradation of the polymer over time. When the PLA composites were immersed in simulated body fluid, an apatite layer was formed on their surface, as verified by Fourier transform infrared, X-Ray Diffraction (XRD), and scanning electron microscopy-EDS, showing that the presence of n-BG induced bioactivity on the PLA matrix. Moreover, the viability of cervical uterine adenocarcinoma cells was higher on PLA/n-BG nanocomposite with 25 wt % of filler. The presence of n-BG barely gave an antibacterial effect on the polymer matrix, despite the well-known biocidal properties of these nanoparticles. Our results show that the presence of n-BGs is a proper route for improving the bioactivity of PLA with potential application in tissue engineering. © 2020 Wiley Periodicals, Inc.